Optical Coherence Tomography Angiography of Purtscher Retinopathy after Severe Traffic Accident in 16-Year-Old Boy - Hassan Hamoudi; Marie Krogh Nielsen; Torben Lykke Sørensen (Case Reports in Ophthalmological Medicine)
Purpose. To describe optical coherence tomography (OCT) angiography (OCTA) in a case of Purtscher retinopathy. Methods. A 16-year-old male underwent ophthalmological examination including color fundus photography, spectral domain OCT, OCTA, and microperimetry. Examination was performed 10 days, 1 month, and 6 months after the trauma. Diagnosis was based on the characteristic clinical presentation. Patients. A single patient case. Results. Only the right eye was affected, and all examinations of the left eye were normal. The visual acuity of the right eye was 0.03 (Snellen equivalent) at 10 days and at one month, improving to 0.16 at 6 months. The imaging confirmed the findings of Purtscher retinopathy with ischemic whitening of the retina and retinal hemorrhages and thickened inner retina on OCT. Microperimetry showed reduced sensitivity in the central macula of the right eye. OCTA revealed nonperfusion in both the superficial and the deep retinal capillary plexus of the right eye. Conclusion. The OCTA in traumatic Purtscher retinopathy following traffic accident showed nonperfusion in both the superficial and the deep capillary plexus of the retina. OCTA is a valuable noninvasive diagnostic examination in Purtscher retinopathy, and fluorescein angiography became redundant in this case.